Effect of Renal or Hepatic Impairment on the Pharmacokinetics, Safety, and Tolerability of Intravenous Rivipansel. Issue 8 (24th June 2020) - Tammara, Brinda K.; Ryan, Kelly; Plotka, Anna; Shafer, Frank E.; Wei, Hua; Readett, David; Fang, Annie; Korth‐Bradley, Joan M.
Abstract: Two studies evaluated the effects of renal and hepatic impairment on pharmacokinetics and safety of rivipansel (NCT02813798, NCT02871570). A single intravenous 840‐mg rivipansel dose was administered to subjects with renal impairment or normal renal function in study 1005 and subjects with moderate hepatic impairment or normal hepatic function in study 1006. Plasma (both studies) and urine (study 1005) samples were collected for 96 hours postdose. All subjects in studies 1005 (n = 28) and 1006 (n = 16) completed all study procedures. Rivipansel exposure (AUCinf ) was 47%, 124%, and 437% higher and total clearance 30%, 57%, and 82% lower in the mild, moderate, and severe renal impairment groups, respectively, than in the normal renal function group. Overall rivipansel exposure was 20% lower and total clearance 31% higher in the moderate hepatic impairment group than in the normal hepatic function group. Ten treatment‐emergent adverse events occurred in studies 1005 and 1006; no event was considered treatment related. As expected, clearance of rivipansel decreased with increasing renal impairment. The difference observed between rivipansel pharmacokinetics in subjects with moderate hepatic impairment and subjects with normal hepatic function was not considered clinically significant. Single doses of rivipansel were well tolerated in subjects with either renal or hepatic impairment.